2020
DOI: 10.1108/ijchm-06-2019-0584
|View full text |Cite
|
Sign up to set email alerts
|

Dining alone: improving the experience of solo restaurant goers

Abstract: Purpose Solo travel for leisure and business is increasing. It is therefore timely to conduct research into the experiences of solo tourists. This paper aims to explore one aspect of the solo tourist experience that can be challenging, that of dining alone. This topic has received little attention in the tourism or hospitality literature. Design/methodology/approach A qualitative approach was adopted and narrative inquiry was selected as the optimum route to obtain detailed and rich accounts of the experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 55 publications
4
44
0
Order By: Relevance
“…The nature of public space exposes solo consumers to social judgement and unwanted gaze, especially when they participate alone in hedonic activities or activities that are traditionally deemed as communal ( Hirschman and Holbrook, 1982 ; Ratner and Hamilton, 2015 ). A recent study by Brown et al (2020) substantiated previous studies by demonstrating how the perceived stigmatisation and negative judgement of other diners cause discomfort on solo diners based on stigma theory. In particular, the study identified the evening meal as the most stressful with the most pronounced social stigma.…”
Section: Literature Reviewsupporting
confidence: 54%
See 4 more Smart Citations
“…The nature of public space exposes solo consumers to social judgement and unwanted gaze, especially when they participate alone in hedonic activities or activities that are traditionally deemed as communal ( Hirschman and Holbrook, 1982 ; Ratner and Hamilton, 2015 ). A recent study by Brown et al (2020) substantiated previous studies by demonstrating how the perceived stigmatisation and negative judgement of other diners cause discomfort on solo diners based on stigma theory. In particular, the study identified the evening meal as the most stressful with the most pronounced social stigma.…”
Section: Literature Reviewsupporting
confidence: 54%
“…Past studies have suggested that solo dining is induced by the circumstances, such as convenience, work schedule, and lack of a dining companion ( Heimtun, 2010 ; Moon et al, 2020 ; Takeda and Melby, 2017 ). For instance, eating out alone is regarded an unavoidable experience for solo travellers ( Brown et al, 2020 ; Heimtun, 2010 ). On the contrary, YouGov, a global market research company, identified enjoying solo time as the key motive to dine alone in the United Kingdom ( Grant, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations